Short-term efficacy and safety of tofacitinib in the treatment of alopecia areata - Zuyan WANG; Junli XUAN; Zhexin WANG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2024)
Objective To investigate the short-term efficacy and safety of tofacitinib in the treatment of alopecia areata. Methods A total of 80 cases of alopecia areata, who visited our hospital from January 2020 to December 2022, were divided into the control and the observational groups according to the lottery method. The controls were given oral prednisone acetate tablet [0.3 mg/ (kg·d)] and topical minoxidil tincture twice daily for 8 weeks, while the patients in the observation group were treated with oral tofacitinib (5 mg/d) and topical minoxidil tincture twice daily. The association of therapeutic efficacy with demographic characteristics, disease duration, clinical classification, hair loss area, hair pulling test results, and family history were also determined. In addition, the clinical efficacy and adverse reactions were compared between the two groups following 4 and 8 weeks of treatment. Results After 8-week treatment, the cure rate in the observation group was higher than that in the controls (60.0% vs. 32.50%, P=0.014). In the observation group, the cure rate was higher in patients with disease duration of ≤7 months than in that with disease duration of >7 months (85.00% vs.35.00%, P=0.001).Moreover, the cure rate was higher in patients with positive hair pulling test than in that with negative hair pulling test(74.07% vs.30.77%, P=0.009). However, the cure rate was not influenced by gender, clinical subtype, area of hair loss and family history. There were no significant differences in the incidence of adverse reactions, including scalp contact dermatitis, mild headache, elevated liver enzymes, and oral herpes simplex between the two groups. Conclusions Tofacitinib is safe for the treatment of alopecia areata, and its efficacy is superior to that of glucocorticoids, especially for those with short disease duration and positive hair pulling test.